ANÁLISE DA MEDIÇÃO DE DESEMPENHO DOS REQUISITOS DE ENGENHARIA PARA OS TRIBUNAIS DE CONTAS ESTADUAIS ALINHADA COM OS PRINCÍPIOS DA INDÚSTRIA 4.0 - Pereira, Flávia Holz Meirelles (2021)
In view of the innovation proposed by the fourth industrial revolution, it is essential to rethink the way in which public institutions act in order to adapt to this current scenario. Specifically in terms of the courts of accounts, initiatives in Brazil, such as the Quality and Agility Program for the Courts of Auditors, instituted by the Association of Members of the Courts of Auditors in Brazil, not only contribute to the Courts of Auditors acting uniformly, as well as improving the quality and speed of audits and judgments. In this sense, reflections lead to ponder on its alignment with the principles of Industry 4.0. The problem, how to analyze the current engineering requirements indicated in the Performance Measurement Framework of the Brazilian Courts of Auditors, which is the evaluation method used by the program, within the scope of engineering inspections, with a focus on alignment with the principles of Industry 4.0. Thus, as a main objective, it was proposited to analyze requirements indicated by the Performance Measurement Framework of the Brazilian Courts of Accounts, within the scope of engineering inspections, based on the principles of Industry 4.0. For the study of the research problem, the following methodological procedure were adopted Use of information from the internal integrated system available at the Court of Auditors of the State of Espírito Santo, analysis of the evidence that was presented as a basis for the attribution of the score indicated in the Measurement Framework of Performance of the Brazilian Courts of Accounts. Access to the data was made available through the database by those responsible for managing this information at the Court of Auditors of the State of Espírito Santo. The theoretical contribution was concentrated on the pillars and principles of industry 4.0, on the quality and agility programs of the courts of account and on their performance measurement frameworks. At the end, it was possible to better understand the result of the evaluation proposed by the program, in the scope of engineering, and to elaborate as a technical product a proposal for a guideline for the selection of innovative “Good Practices” of engineering in line with the principles of Industry 4.0.